Material connexion : the global resource of new and innovative materials for architects, artists and designers - Beylerian, George M.; Dent, Andrew; Moryadas, Anita (London : Wiley, 2005)
From the largest global resource of new materials comes this innovative new book that connects materials to designers' needs. In each of the seven main sections, this highly illustrated book identifies key trends, looks to the future, and helps design professionals select materials with the most potential for their specific projects. By defining a material based on its base composition rather than current use, Material ConneXion allows a designer to fully understand the potential and limitations for a material while conceiving of its new application. Organized to follow the model of the Material ConneXion library, the book's chapters are organized on seven base compositions including: Metals, Glass, Ceramics, Polymers, Natural and naturally derived materials,Carbon-based materials, Cement-based materials. The book includes quotes from 54 leading designers, architects, artists and thinkers worldwide, including Wolfgang Joop, Karim Rashid, Peter Marino, Greg Lynn, Gaetano Pesce, and Philippe Starck, that reflect upon the role of materials in contemporary design and identify their favorite materials. Additionally, the book includes an important reference section with a bibliography, glossary of technical terms, and lists of trade show and professional publication web sites.
Keywords: Architecture and technology; Architecture and technology; Design and technology; Design and technology; Materials--Technological innovations; Materials--Technological innovations